2019
DOI: 10.3390/ijms20153755
|View full text |Cite
|
Sign up to set email alerts
|

Tear Metabolomics in Dry Eye Disease: A Review

Abstract: Dry eye disease (DED) is a multifactorial syndrome that can be caused by alteration in the quality or quantity of the precorneal tear film. It is considered one of the most common ocular conditions leading patients to seek eye care. The current method for diagnostic evaluations and follow-up examinations of DED is a combination of clinical signs and symptoms determined by clinical tests and questionnaires, respectively. The application of powerful omics technologies has opened new avenues toward analysis of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 140 publications
1
47
0
Order By: Relevance
“…Tear samples were analyzed by 1 H NMR spectroscopy at the Faculty of Medicine and Odontology of the University of Valencia (Spain) and by the Institute of Research in Molecular Recognition and Technologic Development of the Polytechnic University of Valencia (Spain) in accordance with previous reports [13-18, 30-32]. For NMR analysis, 20 µL of tear was mixed with 2.5 µL of 90 mM sodium-3-trimethylsilylpropionate- 2,2,3,3-d4 (TSP) in deuterium oxide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tear samples were analyzed by 1 H NMR spectroscopy at the Faculty of Medicine and Odontology of the University of Valencia (Spain) and by the Institute of Research in Molecular Recognition and Technologic Development of the Polytechnic University of Valencia (Spain) in accordance with previous reports [13-18, 30-32]. For NMR analysis, 20 µL of tear was mixed with 2.5 µL of 90 mM sodium-3-trimethylsilylpropionate- 2,2,3,3-d4 (TSP) in deuterium oxide.…”
Section: Methodsmentioning
confidence: 99%
“…Binned data were normalized to total aliphatic spectral area. Available spectral databases and two-dimensional (2D) NMR experiments facilitated the structural identification of the most relevant tear chemical compounds [13-15, 31, 32]. Spectra were processed using MestRenova 6.2 software (Mestrelab Research S.L., Spain) and transferred to MATLAB 7.6 (The MathWorks Inc., Natick, MA, USA) for additional processing/analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A number of methods that determine the quantity and quality of tears, have been used in DES management: slit lamp examination, staining of corneal and conjunctival epithelium with fluorescein, lissamine green, or rose bengal, tear breakup time test, Schrimer test, tear film osmolarity, tear meniscus height, tear protein analysis that measures the lysozyme in the tears, lactoferryn analysis. Recently, abnormally high levels of diadenosine polyphosphate Ap4A I, naturally present in tears, have been found in DES patients 43 . Diadenosine polyphosphates are naturally occurring compounds of the tear, important for the regulation of intraocular pressure and for corneal wound healing.…”
Section: Dry Eye Syndromementioning
confidence: 99%
“…It has been suggested that these substances can be used as biomarkers of DES (ref. 43 ). 1 H NMR-based targeted metabolomic analysis of tear samples of patients with different stage DES and healthy controls before and after 3-month supplementation with antioxidants and omega-3 essential polyunsaturated fatty acids (EPUFA) revealed significant differences in their metabolite profiles.…”
Section: Dry Eye Syndromementioning
confidence: 99%
“…Dry eye (DE) is a multifactorial disease caused by changes in the quality and/or quantity of the precorneal tear film [1]. Current diagnosis of DE is based on a combination of clinical signs, such as those determined by the Schirmer test, tear break-up time (tBUT), and staining scores, as well as symptoms, which are determined by formalized questionnaires.…”
Section: Introductionmentioning
confidence: 99%